Analysis of Stress and Work Motivation on Employee Performance with Work Environment as a Mediation Variable at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan - Menganjur M S; Elfitra Desy Surya (Journal of Research in Social Science and Humanities, 2025)
This study aims to test and analyze the effect of work stress on employee performance. Testing and analyzing work motivation for employee performance.  Testing and analyzing the influence of the work environment on employee performance. To test and analyze the influence of work stress and work motivation on employee performance mediated by the work environment.  This research is a quantitative research with an explanatory approach. The population in this study amounted to 45 people who were directly used as saturated samples. The sample in this study is 45 samples which are saturated samples.  The results of the study are that work stress has a positive and significant effect on the environment of PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. Work motivation has a positive and significant effect on the performance of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. The work environment has a positive and significant effect on the performance of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. Work stress has a positive and significant effect on the performance of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. Work motivation has a positive and significant effect on the performance of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. The work environment has a positive and significant effect on the performance of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan. Work stress and work motivation have a positive and significant effect on the Work Environment of employees at PT PLN Nusantara Power Generation Maintenance Unit (UPHK) Medan